Regular aerobic exercise and blood pressure in East Asians: A meta-analysis of randomized controlled trials - Yutaka Igarashi; Nobuhiko Akazawa; Seiji Maeda (Clinical and Experimental Hypertension, 2018)
The aim of this meta-analysis was to evaluate the effects of regular aerobic exercise on blood pressure in East Asians. The inclusion criteria of the randomized controlled trials were healthy East Asian adults, exercise group performing regular aerobic exercise and control group not exercising, and a description of the mean systolic blood pressure or diastolic blood pressure at rest. This study included 31 study groups and 1994 subjects. Pooled changes in blood pressure showed significant reductions (systolic blood pressure: −4.7 mmHg; diastolic blood pressure: −3.2 mmHg). In subgroup analyses, the change in systolic blood pressure for randomized controlled trials meeting the America Heart Association and American College of Sports Medicine guidelines for physical activity to maintain health was significantly larger than in randomized controlled trials not meeting the guidelines. In addition, meta-regression indicated that the change in systolic blood pressure was significantly related to “exercise time × exercise frequency.” The ideal volume of exercise is that for a long time at a high frequency, such as the volume recommended in the America Heart Association and American College of Sports Medicine guidelines: moderate intensity and >150 min per week. List of abbreviations: BP: blood pressure; BMI: body mass index; SBP: systolic blood pressure; DBP: diastolic blood pressure; RCT: randomized controlled trial; AHA: America Heart Association; ACSM: America College of Sports Medicine; SD: standard deviation; HDL-C: high-density lipoprotein cholesterol; LDL-C: low-density lipoprotein cholesterol; TC: total cholesterol; TG: triglycerides; PEDro: Physiotherapy Evidence Database; CI: confidence intervals; %HRmax: percentage of maximal heart rate.